The influence of the apical dentinal plug on the hermetic seal of endodontically treated root canal - Lansangan, Maria Josefina S.; Trinidad, Rizalinda R.; Jimena, Edna M. (Adviser)+.
This study is concerned with the influence of apical dentinal plug and the distance of the enlargement and obturation of the root canal from the apical foramen on the hermetic seal of an endodontically treated root canal. Fifty dissociated single-rooted human teeth were prepared by filling and reaming. Leakage of these specimens was evaluated by sectioning, placing them in radioisotope solution and distoradiographs. The results from the leakage study show that the influence of a dentinal plug is significant. Perforation of the apical foramen exhibited the severest amount of leakage and the existence of accessory canals might be a contributing factor in the leakage that occurs in the root canal via the apical foramen.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.